The Mediating Role of Job Satisfaction on Gen Z Employees Turnover Intention - Trillian Lim; Yuli Indah Fajar Dini (Universitas Ahmad Dahlan, 2023)
The drastic increase in turnover intention in 2020 was caused by the outbreak of the COVID-19 pandemic, which spread to Indonesia, thus affecting all lines of human life. Some reasons for the intensity of turnover intention are organizational environment, work stress, depression, fatigue, workload, and its effect on employee job satisfaction. This study aims to analyze the impact of work stress and workload on turnover intention with job satisfaction as a mediation role amongst Generation Z employees. The sample in this study was 422 people representing the Generation Z workforce in Batam. PLS-SEM was used to analyze this data. The conclusions of this study indicate that job stress and job satisfaction have a positive effect on turnover intention and job satisfaction; workload has a negative relationship with turnover intention, while job satisfaction mediates the relationship between job stress, workload, and turnover intention.